Reformas judiciales. Informe Ministerio Público. -Fiscalia del Juzgado 2° Superior. -Medellín, 1918, Febrero. - Mora V., José Manuel (Estudios de Derecho, 1917)
Reformas judiciales. Informe Ministerio Público. -Fiscalia del Juzgado 2° Superior. -Medellín, 1918, Febrero.